Effects of exposure in vivo and graded activities on disability and pain related fear and avoidance in chronic low back pain patients (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
The aim of this systematic review was to evaluate the effects of cognitive behavioral interventions “Exposure in Vivo” (EV) and/or “Graded Activity” (GA) to the fear-avoidance beliefs and disability, in chronic low back pain patients. The search strategy was composed by indexed and free terms, had inclusion criteria and included six data bases. The studies were compared considering the design, method, results, evidence level and recommendation grade. Six articles were analyzed: three were randomized control trials and three were single experimental cross case. Four studies indicate that EV reduced fear-avoidance beliefs. Three showed disability reduction after EV in single analyses of each patient. The higher evidence level studies and better recomendation studies (2b, B) support the recommendation of EV to reduce fear-avoi-dance beliefs in chronic low back pain patients. Considering few studies available and methologic limitations is important to amply the exploration about this theme
Keywords: systematic review; pain related fear; disability; low back pain